1984
DOI: 10.1073/pnas.81.3.781
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of nondividing populations of primary human fibroblasts to UV (254 nm) radiation induces a transient enhancement in capacity to repair potentially lethal cellular damage.

Abstract: Nondividing (arrested) populations of primary human fibroblasts from normal individuals exposed to an initial dose (1.5 or 3 J m-2) of far-UV (254 nm) radiation and then incubated in medium containing low (0.5%) serum develop enhanced resistance to inactivation of cloning efficiency by a second (challenge) dose of UV. The resistance develops within 2-4 days, after which there is a decline. Resistance develops to a higher degree and more rapidly (1-2 days) in cells derived from patients with the variant form of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The higher ER ratios found with HSV by Coppey and Menenez (2) may be explained by differences in the experimental protocol or by the fact that growing cultures express higher ER levels than do resting cells (11). Our finding that contact-inhibited resting cells express these conditional responses is in agreement with results from other investigations which show that ER occurs in all stages of the cell cycle, as well as in G-1 arrested cultures (15,16,19).…”
Section: Discussionsupporting
confidence: 93%
“…The higher ER ratios found with HSV by Coppey and Menenez (2) may be explained by differences in the experimental protocol or by the fact that growing cultures express higher ER levels than do resting cells (11). Our finding that contact-inhibited resting cells express these conditional responses is in agreement with results from other investigations which show that ER occurs in all stages of the cell cycle, as well as in G-1 arrested cultures (15,16,19).…”
Section: Discussionsupporting
confidence: 93%
“…In our previous work (Yasuhira et al, 1991), survival experiments suggested that the enhance- ment of PR took 4-8 h after FL-preillumination, although it was not clear how long this enhancement continued. Therefore we first studied the timecourse of the enhancement of PR by using ESS as an endpoint.…”
Section: Resultsmentioning
confidence: 91%
“…The existence of an inducible DNA repair system in higher eukaryotes has been suggested largely from host reactivation studies, but is still controversial (Radman, 1980). Some recent works showed that pretreatment of eukaryotic cells with UV or other agents augmented some kind of repair systems in terms of the recovery of their own survival (Tyrrell, 1984;Chao and Lin-Chao, 1987). It was also reported independently that such DNA damaging agents induce the synthesis of a series of proteins (Ruby and Szostak, 1985;Kartasova et al, 1987), but it is not clear whether such proteins are involved in the DNA-repair process.…”
Section: Discussionmentioning
confidence: 99%
“…Defects in the latter result in increased cell death. 1 On the other hand, specific signal transduction pathways including activation of protein kinases and transcription factors are also induced by ultraviolet irradiation (UV). 2,3 Previous studies have shown that one of the earliest post-UV responses is activation of tyrosine kinases such as Src, 4 EGF-receptor, 5 insulin receptor, 6 Syk 7 and ZAP-70.…”
Section: Introductionmentioning
confidence: 99%